Actividad turística y su relación con el impacto cultural en la ciudad de Nauta, 2022 - Vargas Pinedo, Tonny Manuel (2023)
The general objective is to establish if there is a positive and notable connection between tourist activity and the cultural impact in the city of Nauta, using a method with a quantitative approach; The most important result is that it shows .659** Pearson corresponding to a medium positive correlation and whose sigma is 0.00 less than 0.05, concluding that there is a notable link between both variables.